Dams and Climate Interact to Alter River Flow Regimes Across the United States - Dol Raj Chalise; A. Sankarasubramanian; Albert Ruhi (Earth's Future, 2021)
Abstract Storing and managing river flows through reservoirs could dampen or increase climate‐induced fluctuations in streamflow, but interactions between the effects of dams and climate are poorly understood. Here, we examined how dam properties control different facets of flow alteration across the coterminous United States (CONUS), and compared alteration trends between dam‐affected and reference stream gages. We quantified departures from the natural flow regime using 730 stations with long‐term daily discharge data. Dam size and purpose explained high variation in flow alteration, and alteration was particularly severe in water‐stressed regions. Importantly, regulation of river flows by dams often dampened climate‐driven alteration (48% of the flow metrics), particularly in watersheds with positive flow trends; while worsening climatic impacts in other cases (44%), or even having dual effects (8%). Our results show that dam and climate impacts on streamflow need to be assessed jointly, and based on a diverse range of flow regime facets (e.g., event magnitude and duration, frequency, and timing) instead of mean annual flows only. By pairing the USGS streamflow records available from upstream and downstream of 209 dams across the CONUS, we advance the notion that dams amplify flow alteration, but also ameliorate some flow alteration metrics. Understanding such potential and limitations is important in light of climate non‐stationarity and a new wave of damming in developing economies, and will be key to further advancing environmental flow science into the future.